Le désir sexuel des femmes, du DSM à la nouvelle médecine sexuelle - Marilène Vuille (Genre, Sexualité et Société)
« Sexual desire disorders » first appear in the Diagnostic and Statistical Manual of Mental Disorders (DSM-III) in unisex form in 1980. Through successive revisions of the manual up to the current one, a specifically female sexual desire emerges as a distinct entity. It is defined as more complex that the now exclusively male sexual desire. The DSM’s current approach to female sexual desire and its « dysfunctions » can be shown to be derived from a circular model put forth by medical sexologists in the beginning of the 2000s to provide a construct of women’s sexual desire. Since then, this particular conceptualization has been broadly adopted as a basis for debate in international circles of the field of sexology. The model itself has actually become the point of convergence of a body of knowledge on sexuality produced by different disciplinary fields. It serves as an anchor for the co-production of categories as well as of diagnostic criteria and it underlies new trends in neurological and pharmacological research. It is also one of the specific tools used in the construction of a new « sexual medicine » that seeks recognition as a fully-fledged medical specialty.